EFL students’ perceptions of self-created glossaries in Translation Class - Nengsih, Izam Zulfa; Ardi, Havid (Journal of English Language Teaching, 2025)
This study investigates EFL students’ perceptions of self-created glossaries as a strategy to enhance vocabulary mastery for translation tasks in an Indonesian-English translation class at Universitas Negeri Padang. The research focus on four aspects of perception, namely attractiveness, perceived effectiveness, relevance, and perceived motivation, and also explores the strategies students used in developing their glossaries. The participants were 25 students enrolled in the 2024/2025 Indonesian-English Translation class who completed weekly glossary assignments. Data were collected through a questionnaire consisting of 20 closed-ended and one open-ended item and analyzed using descriptive quantitative and thematic approaches. The results indicate that students generally held positive perceptions of the self-created glossaries (M = 2.94 on a 4-point scale). Students who applied more varied and systematic strategies, such as contextual vocabulary selection and organized structuring, reported higher levels of perceived usefulness and motivation. These findings suggest that self-created glossaries can effectively support vocabulary learning, and enhance students’ preparation for translation activities.